Intimate Organ (Vaginal) Hygiene on Knowledge and Behavior During Menstruation in Girls at SMP Negeri 12 Kec. Tamalanrea, Makassar City, South Sulawesi - Dewi Parwati; Susanti; Zumrotul Ula; Samila; Lumastari Ajeng Wijayanti; Hartaty (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Background: Cleanliness of the genital area, especially during menstruation, is often ignored by women. During menstruation, blood and sweat come out and stick to the vulva, which can cause the genital area to become damp. Objective: The aim of this research is to determine the relationship between knowledge and vulva hygiene behavior during menstruation in girls at SMP Negeri 12 Kec. Tamalanrea, Makassar City, South Sulawesi. Method: This research uses a correlation research design with a cross sectional approach. Data collection uses questionnaires. Data analysis uses univariate and bivariate data analysis. Results: The results of the study showed that almost half had good knowledge (39.75%), half had sufficient knowledge (50%), and a small number of respondents had poor knowledge (11.25%). The majority behaved well (85%) and a small proportion of respondents behaved badly (15%). Conclusion: it was found that there was a relationship between knowledge and vulva hygiene behavior during menstruation in girls at SMP Negeri 12 with a p value of 0.000.